Correlation between Carbonic Anhydrase Isozymes and the Evolution of Myocardial Infarction in Diabetic Patients - Sorina Magheru; Calin Magheru; Florin Maghiar; Liliana Sachelarie; Felicia Marc; Corina Maria Moldovan; Laura Romila; Anica Hoza; Dorina Maria Farcas; Irina Gradinaru; Loredana Liliana Hurjui (Biology, 2022)
(1) Background: Myocardial infarction was, until recently, recognized as a major coronary event, often fatal, with major implications for survivors. According to some authors, diabetes mellitus is an important atherogenic risk factor with cardiac determinations underlying the definition of the so-called “diabetic heart”. The present study aims to establish a correlation between the evolution of myocardial infarction in diabetic patients, by determining whether lactic acid levels, the activity of carbonic anhydrase isoenzymes, and the magnitude of ST-segment elevation are correlated with the subsequent evolution of myocardial infarction. (2) Methods: The study analyzed 2 groups of 30 patients each: group 1 consisted of diabetic patients with acute myocardial infarction, and group 2 consisted of non-diabetic patients with acute myocardial infarction. Patients were examined clinically and paraclinical, their heart markers, lactic acid, and the activity of carbonic anhydrase I and II isozymes were determined. All patients underwent electrocardiogram and echocardiography analyses. (3) Results: The results showed that diabetics develop acute myocardial infarction more frequently, regardless of how much time has passed since the diagnosis. The value of myocardial necrosis enzymes was higher in diabetics than in non-diabetics, and acute coronary syndrome occurs mainly in diabetics with poor metabolic balance. Lethality rates in non-diabetic patients with lactic acid values above normal are lower than in diabetics. (4) Conclusions: Lactic acid correlated with the activity of isozyme I of carbonic dioxide which could be early markers of the prognosis and evolution of diabetic patients with acute myocardial infarction.